Penerapan Manajemen Risiko untuk Meminimalisasi Pembiayaan Bermasalah di Koperasi Bina Usaha Negara Lahat - Jalaludin Jalaludin (Journal of Management and Bussines (JOMB), 2021)
This study aimed to analyze non-performing financing in the Kota Negara Lahat City Development Cooperative and to determine the application of risk management to minimize non-performing financing in the Kota Negara Lahat Business Development Cooperative. The method used is descriptive method. Analysis of the data used is data reduction, data display, and drawing conclusions. Triangulation testing is done by checking the data to the same source with different techniques. The results showed that the steps used by the State Lahat City Business Development Cooperative to prevent the occurrence of non-performing financing were contained in every action starting from before the financing occurred until the financing was completed. The prevention of problem financing starts before the customer takes the financing, in which the Kota Negara Lahat Cooperative of Bina Usaha Kota Negara Lahat applies the precautionary principle in every action, especially in the distribution of financing because the risks that often occur are found in financing transactions in the Kota Negara Lahat Cooperative. the. In conclusion, the Kota Negara Lahat Business Development Cooperative has taken several ways to overcome or prevent the occurrence of problematic financing customers. The rapid development of the external and internal environment of cooperatives has resulted in increasingly complex risks for cooperative business activities. Keywords: Non-performing Financing, Application of Risk Management